Optimizing clinical outcomes in polypharmacy through poly-de-prescribing: a longitudinal study - Garfinkel, Doron; Levy, Yuval (Frontiers in Medicine, 2024)
Objectives: To evaluate in older people with polypharmacy, whether the number of medications de-prescribed correlates with the extent of improvement in Quality of life (QoL) and clinical outcomes.A prospective longitudinal cohort study in community-living people with polypharmacy in Israel.Participants age 65 or older who took at least six prescription drugs were followed for at least 3 years (range 3 -10) after recommendations for poly-deprescribing (PDP).PDP recommended at first home visit using the Garfinkel Algorithm. Annual follow up and end of study questionnaires assessing clinical outcomes, QoL and satisfaction from deprescribing. We recorded all medications taken, complications, hospitalizations and mortality.307 participants met the inclusion criteria; 25 incomplete end-of study questionnaires leaving 282 participants for subjective analysis. Participants were divided into 2 subgroups, those who discontinued more than 50% of the drugs (PDP group) or less than 50% (nonresponders-NR).Objective: 3 years survival rate and hospitalizations. Subjective: general satisfaction from deprescribing, change in functional, mental and cognitive status, sleep quality, appetite, continence, pain.Results: Mean age 83 (range 65-99). Mean number of drugs at baseline visit 9.8 (range 6-20), 6.7±2.0 deprescribed in the PDP group (n=146), 2.2±2.1 in the NR (n=161) (P<0.001).No statistical difference between the groups in 3 years survival rate and hospitalisationshospitalizations; there was a significant improvement in functional and cognitive status and in general satisfaction from the intervention in the PDP compared to the NR group. Improvement was usually evident within 3 months, persisted for several years.Poly de-prescribing in older population, has beneficial effects on several clinical outcomes with no detrimental effect on rate of hospitalization and survival. The